"I Feel Suffocated:" Understandings of Climate Change in an Inner City Heat Island. Issue 6 (1st November 2016) - Singer, Merrill; Hasemann, Jose; Raynor, Abigail
ABSTRACT: Global climate change is contributing to a range of adverse environmental and weather shifts, including more intense and more frequent heatwaves and an intensification of the urban heat island effect. These changes are known to produce a set of significant and differentially distributed health problems, with a particularly high burden among poor and marginalized populations. In this article, we report findings from a qualitative study of community knowledge, attitudes, health and other concerns, and behavioral responses regarding mounting urban temperatures and related environmental health issues among Latinos living in the city of Hartford, CT in northeast United States. Findings suggest the need for enhanced participation in knowledge dissemination and preparedness planning based on the coproduction of knowledge about climate change and community responses to it. The special role of anthropology in such efforts is highlighted.